Cardiac and Hemodynamic Manifestations of Hereditary Hemorrhagic Telangiectasia - Farhan, Ahmed; Latif, Muhammad A.; Minhas, Anum; Weiss, Clifford R. (International Journal of Angiology, 2022)
The autosomal dominant trait hereditary hemorrhagic telangiectasia (HHT) causes multiorgan dysplastic lesions of the vasculature that can activate multiple physiological cascades leading to a broad array of cardiovascular diseases. Up to 78% of patients with HHT develop hepatic arteriovenous malformations (AVMs), which cause a hyperdynamic circulatory state secondary to hepatic/portal shunting. This condition can eventually progress to high-output cardiac failure (HOCF) with continued peripheral tissue hypoxemia. Treatment for HOCF is often limited to supportive measures (diuretics and treatment of anemia); however, recent studies using systemic bevacizumab have shown promise by substantially reducing the cardiac index. In the context of liver AVMs and high cardiac output, the pulmonary vasculature can also experience high flow. Without adequate dilation of pulmonary vessels, post-capillary pulmonary hypertension can develop. Another form of pulmonary hypertension observed in HHT, pulmonary arterial hypertension, is caused by HHT-related mutations in ENG and ACVRL1 causing congestive arteriopathy. Post-capillary pathogenesis is addressed by reducing the high-output state, whereas the pre-capillary state is treated with supportive mechanisms (diuretics, oxygen) and agents targeting pulmonary vasoreactivity: endothelin-1 receptor antagonists and phosphodiesterase-5 inhibitors. If either form of pulmonary hypertension is left untreated or proves refractory and progresses, the common hemodynamic complication is right heart failure. Targeted right heart therapies involve similar strategies to those of pulmonary arterial hypertension, with several experimental approaches under study. In this review, we describe in detail the mechanisms of pathogenesis, diagnosis, and treatment of the hemodynamic complications and associated cardiovascular diseases that may arise in patients with HHT.
Keywords: arteriovenous malformations; high-output cardiac failure; right heart failure; hereditary hemorrhagic telangiectasia; pulmonary hypertension; angiodysplastic lesions; atrial fibrillation